Bath Abbey
The great five-light south transept window, which is taken up to the full height of the nave, is filled with modern glass, a thank offering for the recovery of Edward VII from typhoid fever. Its horizontal transoms cut the vertical mullions at intervals which serve to accentuate the height. Similar optical corrections were applied to the other major windows. The American flag stands as an honor to soldiers who served in two World Wars.